Pemaknaan Generasi Z terhadap Lagu Taruh Karya Nadin Amizah sebagai Narasi Tandingan Tren Marriage is Scary - Agil Siti Khomariyah; Thriwaty Arsal (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2026)
The “Marriage is scary” phenomenon gaining traction on social media is influencing how Generation Z views romantic relationships and marriage. Amid the dominance of this narrative, Nadin Amizah’s song “Taruh” emerges as a form of popular culture that offers a different perspective on love, fear, and hope within relationships. This study aims to understand how Generation Z interprets the song “Taruh” and how this interpretation presents an alternative perspective on the “Marriage is scary” trend. The study employs a qualitative method with a phenomenological approach to explore the subjective experiences of Generation Z students at Semarang State University. Data were collected through in-depth interviews and observations involving informants who had listened to the song “Taruh” and understood the “Marriage is scary” trend. The results indicate that the song “Taruh” is interpreted as a representation of relationships that contain fear, trauma, and uncertainty, yet still leave room for hope and courage in love. The song is understood as a counter-narrative that helps Generation Z view relationships more realistically and not be entirely pessimistic about marriage.